Fiscal decentralization and subnational fiscal autonomy in Brazil: Some facts of the nineties - Mônica Mora; Ricardo Varsano (Institute for Applied Economic Research (ipea), 2015)
This paper considers some facets of the recent Brazilian experience in fiscal decentralization. For this purpose, it describes the pattern of fiscal decentralization in Brazil and, subsequently, discusses some events of the nineties pertaining to fiscal relations in the federation. Historically, Brazilian experience with fiscal federalism has been marked by ups and downs in the degree of fiscal decentralization. Satisfactory conciliation between the need to ensure a reasonable degree of financial autonomy for subnational governments, on one hand, and the requirement of coordinating fiscal instruments in order to serve national interests, on the other, has not yet been attained. The analysis of events of the nineties does not reveal a consolidated model of federalism but a transition process characterized by attempts to correct the aftermath of both excessive centralization and immoderate decentralization experienced in sequence in the past. The paper concludes that preservation of fiscal decentralization may require the imposition of restrictions on the autonomy of subnational governments, this time for economic rather than for political reasons.
Keywords: 330